Effect of moderate prenatal ethanol exposure on the differential expression of two histamine H3 receptor isoforms in different brain regions of adult rat offspring - Davies, Suzy; Lujan, Kiana S.; Rappaport, Ella J.; Valenzuela, Carlos F.; Savage, Daniel D. (Frontiers in Neuroscience, 2023)
We have reported that prenatal alcohol exposure (PAE) elevates histamine H3 receptor (H3R) agonist-mediated inhibition of glutamatergic neurotransmission in the dentate gyrus. Here, we hypothesized that PAE alters the expression of two prominent H3R isoforms namely, the rH3A and rH3C isoforms, which have differing intrinsic activities for H3R agonists, in a manner that may contribute to heightened H3R function in PAE rats. In contrast to our predictions, we found different effects of sex and PAE in various brain regions with significant interactions between sex and PAE in dentate gyrus and entorhinal cortex for both isoforms. Subsequently, to confirm the PAE-and sex-induced differences on H3R isoform mRNA expression, we developed a polyclonal antibody selective for the rH3A inform. Western blots of rH3A mRNA-transfected HEK-293 cells identified a 48 kDa band of binding consistent with the molecular weight of rH3A, thus confirming antibody sensitivity for rH3A protein. In parallel, we also established a pan-H3R knockout mice line to confirm antibody specificity in rodent brain membranes. Both qRT-PCR and H3R agonist-stimulated [35S]-GTPγS binding confirmed the absence of mH3A mRNA and H3 receptor-effector coupling in H3R knockout (KO) mice. Subsequent western blotting studies in both rat and mouse brain membranes were unable to detect rH3A antibody binding at 48 kDa. Rather, the H3RA antibody bound to a 55 kDa band in both rat and mouse membranes, including H3R KO mice, suggesting H3RA binding was not specific for H3Rs in rodent membranes. Subsequent LC/MS analysis of the 55 kDa band in frontal cortical membranes identified the highly abundant beta subunit of ATPase in both WT and KO mice. Finally, LC/MS analysis of the 48 kDa band from rH3A mRNA-transfected HEK-293 cell membranes was able to detect rH3A protein, but its presence was below the limits of quantitative reliability. We conclude that PAE alters rH3A and rH3C mRNA expression in some of the same brain regions where we have previously reported PAE-induced alterations in H3R-effector coupling. However, interpreting the functional consequences of altered H3R isoform expression was limited given the technical challenges of measuring the relatively low abundance of rH3A protein in native membrane preparations.